(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The article provides a comprehensive study of the theoretical and practical aspects of forming a digital communication culture among future teachers in the higher pedagogical education system under conditions of global digitalization. The relevance of the research is determined by the necessity for modern educators to adhere to professional ethical standards in virtual spaces, apply emotional intelligence in cyber-communication, and organize efficient information exchange with students.